Study guides

☆☆

Q: How do you solve 3y 5 equals 11?

Write your answer...

Submit

Related questions

x = 5, y = -1

3y + 8 = 3 -8 -8 3y=-5 (3y)/3=-5/3 y=(-5/3)

2x-11

x+3y=2 x= -5 y = 1

10y= 6y+5+3y 10y=6+9y y=6

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

Solve for y.2x - 3y = 52x - 2x - 3y = -2x + 5-3y = -2x + 5-3y/-3 = -2x/-3 + 5/-3y = (2/3)x - 3/5Clearly you see that the slope is 2/3.

Add the two equations together. The x disappears. 2y - x = 3 + x = 3y - 5 ------------------------ 2y = 3y -2 Can you finish it from there?

5x - y = 55x - 3y = 15from the first equation:5x = 5 + y , substitute it in the second equation:5 + y - 3y = 155 -2y = 15-2y = 15 - 5-2y = 10y = -5Now,solve for x :5x = 5 +y5x = 5 -5 = zerox = zero

3y + 2y + 4 + 1 = 805y + 5 = 805y = 75y = 15

5 - 2y = -3y - 2Subtract 5 from each side:-2y = -3y - 7Add 3y to each side:y = -7

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

You have 2 equations and 2 unknowns so you can solve 2x-3y = -11 y = 4x -3 2x - 3y = -11 -4x + y = -3 multiply 1st equation by 2 both sides: 4x-6y = -22 -4x + y = -3 add: -5y = -25 y = 5 substitute y = 5 into either equation: -4x+y = -3 -4x +5 = -3 -4x = -8 x = 2

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8

5 - 2y = 3y - 5 10 = 5y So, y = 2.

x=1, y=1

4y + 4 = 3y - 5 y = -9

If: 5x-3y = -34 then y = 5/3x+34/3 as a straight line equation whereas 5/3 is the slope and 34/3 is the y intercept

(3y + 5)(y - 2)

It can't be answered. You need the same variables on both sides. Example: 3y+5x=5 1/2 x (etc.)

Yes.

y=5

-x+3y=5-x-3y=1break apart the equation by setting the two variable expressions equal to 1-x+3y=1 and 5-x-3y=1now in the seperate equations, combine all like terms-x+3y=1 and -x-3y=-4now the choice is yours you can choose to solve for x by eliminating y or vice versa. i'll solve for yyou want to first line up the equations vertically with corresponding like terms-x+3y=1-x-3y=-4 to eliminate x subtract one equation from the other(bottom-top)= new bottom equation-x+3y=1-6y=-5y= 5/6-x+3(5/6)=1 subsitiute 5/6 for yx= 3/2 and y= 5/6

If 2x + 5 = 11, then 11 - 5 = 2x 6 = 2x 3 = x

-3y+5=-4 subtract 5 from each side of the equation: -3y=-9 Divide by -3 to get the variable alone:y=3